Proceedings of the 2015 6th International Conference on Manufacturing Science and Engineering 2015
DOI: 10.2991/icmse-15.2015.281
|View full text |Cite
|
Sign up to set email alerts
|

Research on Electromagnetic Scattering Characteristics and Radar Cross Section Reduction of Vertical tail

Abstract: Method of Moment is used to calculate vertical tail's radar cross section(RCS). The impact of leading-edge sweep angle, span and inclination on vertical tail's RCS is analyzed and then vertical tail's RCS curves and function expressions with leading-edge sweep angle,span and inclination are fitted by the calculation results.The results show that by optimizing the vertical tail leading-edge sweep angle, span, inclination and other geometrical parameters, can improve the stealth performance of the vertical tail.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Kang et al used the precise integration time-domain (PITD) method instead of the Finite-Difference Time-Domain (FDTD) method to study the propagation in magnetized plasma [14]. On the other hand, the RCS is a physical quantity to characterize the echo intensity of the target irradiated by the radar wave and is of great importance in studying scattering characteristics [15,16]. Theoretical studies on RCS and scattering characteristics in a certain frequency band have been reported [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Kang et al used the precise integration time-domain (PITD) method instead of the Finite-Difference Time-Domain (FDTD) method to study the propagation in magnetized plasma [14]. On the other hand, the RCS is a physical quantity to characterize the echo intensity of the target irradiated by the radar wave and is of great importance in studying scattering characteristics [15,16]. Theoretical studies on RCS and scattering characteristics in a certain frequency band have been reported [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%